Effectiveness of Schoology Learning Media During the Covid-19 Pandemic - Husnarika Febriani; Khairuna Khairuna; Yuli Surya Rezeki Hutagalung (Journal of Education and Teaching Learning, 2022)
This study aims to find out how the application and effectiveness of schoology learning media during the Covid-19 pandemic on biology learning outcomes at MTS Al-Wasliyah Tembung. This research is a qualitative research using case study method. The subjects of this study were the vice principal, teachers of science studies, and 85 students of class IX science at MTS Al-Wasliyah Tembung. The instrument used to collect data was by interviewing the vice principal and biology teachers. While the students used a questionnaire for class IX science students as many as 15 items and the results of learning biology on genetic material. Based on the results of this study, it was found from interview data, questionnaires and grades obtained by students in science subjects, especially in genetic material, which was above the KKM with a value of 70, where class IX-3 consisted of 40 students with an average value of 75.75 and class IX-3 IX-5, which consists of 45 students with an average score of 77.22 and the effectiveness of the use of schoology conducted by MTS Al-Wasliyah Tembung during the covid-19 pandemic is 72% and has been running effectively. While the inhibiting factor for learning schoology during the covid-19 pandemic was because students did not have android phones which had an impact on students' delays in joining classes. In addition, the internet network and data packages are also a problem for students at MTS Al-Wasliyah Tembung.